2015
DOI: 10.1152/ajpcell.00280.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RhoA-dependent pathway and contraction by endogenous hydrogen sulfide in rabbit gastric smooth muscle cells

Abstract: Inhibitory neurotransmitters, chiefly nitric oxide and vasoactive intestinal peptide, increase cyclic nucleotide levels and inhibit muscle contraction via inhibition of myosin light chain (MLC) kinase and activation of MLC phosphatase (MLCP). H2S produced as an endogenous signaling molecule synthesized mainly from l-cysteine via cystathionine-γ-lyase (CSE) and cystathionine-β-synthase (CBS) regulates muscle contraction. The aim of this study was to analyze the expression of CSE and H2S function in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 57 publications
4
33
0
1
Order By: Relevance
“…In the present work, the inhibitory effects of H 2 S on spontaneous contractions (EC 50 = 329.2 M) and EFS-induced cholinergic or tachykinergic contraction (EC 50 = 2 mM and 5.7 mM respectively) have been observed when high concentrations have been added to the bath. However, despite these relatively high concentrations, our results demonstrate that H 2 S inhibitory effects are reversible, so they may not be related to an irreversible impairment of tissue function due to toxicity as it has also been shown in isolated smooth muscle cells [21]. Moreover, prior studies have reported that even if H 2 S concentration in the external medium is high, concentration inside the tissue may be much lower, or even trivial [1].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In the present work, the inhibitory effects of H 2 S on spontaneous contractions (EC 50 = 329.2 M) and EFS-induced cholinergic or tachykinergic contraction (EC 50 = 2 mM and 5.7 mM respectively) have been observed when high concentrations have been added to the bath. However, despite these relatively high concentrations, our results demonstrate that H 2 S inhibitory effects are reversible, so they may not be related to an irreversible impairment of tissue function due to toxicity as it has also been shown in isolated smooth muscle cells [21]. Moreover, prior studies have reported that even if H 2 S concentration in the external medium is high, concentration inside the tissue may be much lower, or even trivial [1].…”
Section: Discussionsupporting
confidence: 63%
“…In the respiratory system, H 2 S reversibly inhibited acetylcholine (ACh)-induced calcium oscillations responsible for the contraction of airway SMCs [19]. Similar findings have been reported in guinea-pig ileum, rat jejunum and rabbit stomach, where H 2 S significantly reduced cholinergic mediated contractions [15,20,21].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…; Nalli et al. ). Briefly, colonic circular muscle strips were incubated for 30 min at 31°C in 15 mL of HEPES medium (120 mmol/L NaCl, 4 mmol/L KCl, 2.6 mmol/L KH 2 PO 4 , 0.6 mmol/L MgCl 2 , 25 mmol/L HEPES, 14 mmol/L glucose, 2.1% (v/v) Eagle's essential amino acid mixture, 0.1% collagenase [type II], and 0.1% soybean trypsin inhibitor).…”
Section: Methodsmentioning
confidence: 98%
“…; Nalli et al. ). Smooth muscle cells were homogenized in lysis buffer containing Triton X‐100 and protease and phosphatase inhibitors.…”
Section: Methodsmentioning
confidence: 98%